1986
DOI: 10.1007/bf00194602
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of 4′-deoxydoxorubicin (esorubicin) in hormone resistant prostate cancer

Abstract: Fifteen patients with hormone resistant advanced prostate cancer were treated with anthracycline analog 4'-deoxydoxorubicin (Esorubicin). No patient had objective evidence of tumor regression. Six patients (40%) were classified using the National Prostatic Cancer Project criteria as having stable disease after two courses of therapy. Treatment was associated with significant hematologic toxicity with 50% of patients experiencing grade III or IV neutropenia. Clinical cardiac toxicity was not observed. Further t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1988
1988
1993
1993

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Phase II clinical trials using esorubicin in a variety of tumors have now been completed [1,[5][6][7][8][9][10][11]. Although modest clinical activity has been reported in malignant lymphoma [5] and breast cancer [11], other clinical reports have been disappointing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phase II clinical trials using esorubicin in a variety of tumors have now been completed [1,[5][6][7][8][9][10][11]. Although modest clinical activity has been reported in malignant lymphoma [5] and breast cancer [11], other clinical reports have been disappointing.…”
Section: Discussionmentioning
confidence: 99%
“…Based on in vitro and animal data, esorubicin appeared to possess a broader spectrum of clinical activity and less myocardial toxicity than doxorubicin [2][3][4]. Several studies have described the drug's antitumor activity in patients with advanced cancer [5][6][7][8][9][10][11] with the suggestion that clinical and subclinical myocardial toxicity may occur in human subjects [12][13][14]. We report the cardiotoxicity observed from esorubicin in two phase II clinical trials conducted by the Cancer and Leukemia Group B (CALGB) [6,71.…”
Section: Introductionmentioning
confidence: 99%
“…Phase II trials demonstrated some activity for esorubicin in colorectal cancer, breast cancer and multiple myeloma [8][9][10]. No activity was noted in trials of non-small cell lung cancer, melanoma, renal cell carcinoma, prostate cancer, or head and neck cancer [11][12][13][14][15]. As more experience with the drug was accumulated, evidence of cardiotoxic effects were noted [16].…”
Section: Introductionmentioning
confidence: 99%